أثر التدقيق الخارجي على جودة المعلومــة الماليــة _دراسة ميدانية ببنك الفلاحة و التنمية الريفية B.A.D.R- بأدرار (مجلة الواحات للبحوث والدراسات, 2017)
This Study Is Involved In The Field Studies That Aim To Identify The Extern Auditing Impact On The Financial Information's Quality Throughout A Questionnaire Addressed To  Agriculture And Rrural Development Bank Employees Then,Generalizing The Fundings On The Sample Study We Have Adopted A Descriptive Approach To Describe The External Auding And The Financial Information Quality As Well As The Previous Studies Which Dealt With Such A Topic And Even The Inductive Appoach To Study Its Impact On The Financial Information Qualiwe Questioned 37 Informants Who Had Given Their Opinion Upon The Independence's Impact, The Auditing Honesty And The Scientific Qualification On The Financial Information Qualityty In This Bank  In Addition To The Clarification Of The Auditor Report On The Features That Enrich The The Financial Information Quality And Effects The Employees Decisions Effectivel We Conclude That The External Auditing Importance Is Lie In Creating An Extra Value To The Company Through Increasing The Its Financial Information Effectiveness And Its Value Key Words   -  External Auditing, Financial Information Features,Financial Information Quality,Financial Lists